Analysis of the Use of BOS Funds in Creating Effective Schools (Case Study at SDN Palipurna) - H. Soro , Suharyanto; Astuti, Dini; Juhariah, Cucu (Civiliza Publishing, Indonesia., 2025)
The use of fund (money) at school is still a problem for its management. One of the function of fund is to support the school financial so that can be reached the aim of those schools. The focus of the research includes planning, implementation, evaluation, and follow-up of Dana BOS usage. This study aims to analyze the utilization of School Operational Assistance Fund (Dana BOS) in realizing effective schools at SDN Palipurna, Ibun District, Bandung Regency.This study employs a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation, and analyzed descriptively. The results indicated that the planning of Dana BOS is conducted participatively and oriented towards improving the quality of learning. The implementation of Dana BOS follows the planned priorities, focusing on the development of infrastructure and learning activities. Evaluation is carried out periodically involving the school committee and community to ensure transparency and accountability. The follow-up on evaluation results is used as a basis for improving the management of Dana BOS to be more effective and efficient. Thus, the management of Dana BOS at SDN Palipurna positively contributes to realizing an effective and quality school.